2019
DOI: 10.1097/mcg.0000000000000978
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Health-related Quality of Life in Irritable Bowel Syndrome Patients Compared With Healthy Individuals

Abstract: GI symptom severity and anxiety correlate with PCS, whereas psychosocial/somatic measures parallel MCS. However, HRQOL is comparable in IBS and HCs when perceived stress, somatic symptom severity, and mindfulness are at optimal levels. These findings may have important implications in the management of IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 62 publications
(71 reference statements)
3
34
1
1
Order By: Relevance
“…The data reported here suggest that concurrent, but not baseline, psychological comorbidities are more predictive of this impaired long‐term quality of life than GI symptom severity. Several studies in IBS have found similar results, in particular for the mental health‐related quality of life; that is, Naliboff et al reported that psychological distress had a stronger effect on health‐related quality of life than GI symptoms, Koloski et al reported that depression was independently associated with mental quality of life, and Addante et al reported that perceived stress, and anxiety and depression were significant predictors for mental health‐related quality of life . This raises the question whether current treatment goals for IBS in daily clinical practice should be revised.…”
Section: Discussionmentioning
confidence: 87%
“…The data reported here suggest that concurrent, but not baseline, psychological comorbidities are more predictive of this impaired long‐term quality of life than GI symptom severity. Several studies in IBS have found similar results, in particular for the mental health‐related quality of life; that is, Naliboff et al reported that psychological distress had a stronger effect on health‐related quality of life than GI symptoms, Koloski et al reported that depression was independently associated with mental quality of life, and Addante et al reported that perceived stress, and anxiety and depression were significant predictors for mental health‐related quality of life . This raises the question whether current treatment goals for IBS in daily clinical practice should be revised.…”
Section: Discussionmentioning
confidence: 87%
“…However, we believe that the management of digestive symptoms should be considered in our efforts to improve the quality of life of CAI patients. Indeed, studies on IBS patients have demonstrated that the severity of GI symptoms is negatively associated with the “physical” dimension of health-related quality of life 28 and that the patient quality of life depends on IBS subtype, diarrhea have lower disease specific quality of life than constipation 29 .…”
Section: Discussionmentioning
confidence: 99%
“…IBS is further classified by the predominant stool form observed during >25% of bowel movements: IBS with constipation (IBS-C), IBS with diarrhea (IBS-D), and IBS with mixed bowel habits [1]. Patients with IBS often have impairments in quality of life [3,4]. Indeed, the severity of IBS symptoms was shown to be associated with daily activity impairment [4].…”
Section: Introductionmentioning
confidence: 99%